Peran Sukuk dalam Stabilitas Moneter di Indonesia - Abdul Aziz Mizanul Amal; Abdurrahman Faiz; Muhammad Adi Bintara; Rasidah Novita Sari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Sukuk as an Islamic financial instrument plays a strategic role in supporting monetary stability in Indonesia. This study explores the relationship between sukuk and monetary policy variables, such as inflation, exchange rate, and economic growth. Sukuk has proven to be a stable instrument that supports sustainable development by mitigating external debt risks. Through the analysis of the monetary policy transmission mechanism, this study identifies the role of sukuk in asset price and exchange rate channels. The results show that sukuk has a positive impact on monetary stability and long-term economic growth.